2012
DOI: 10.1371/journal.pone.0040434
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Cancer Cells Enhance the Ability of Collagen Internalization during Epithelial–Mesenchymal Transition

Abstract: BackgroundExtracellular matrix (ECM) remodeling is predominantly mediated by fibroblasts using intracellular and extracellular pathways. Although it is well known that extracellular degradation of the ECM by proteases derived from cancer cells facilitates cellular invasion, the intracellular degradation of ECM components by cancer cells has not been clarified. The aim of this study was to characterize collagen internalization, which is the initial step of the intracellular degradation pathway in pancreatic can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 37 publications
4
26
0
Order By: Relevance
“…Indeed, CRK phosphorylation was increased in YSF MEF, indicating that lack of Src may lead to a compensatory upregulation of c-abl with ensuing increase in matrix macropinocytosis in these cells. Although most of our studies were performed in the absence of TGF-␤1 stimulation, the signaling networks we studied are classically downstream from TGF-␤1 stimulation, and this growth factor did stimulate collagen internalization in our studies and in prior studies (18).…”
Section: C628mentioning
confidence: 49%
“…Indeed, CRK phosphorylation was increased in YSF MEF, indicating that lack of Src may lead to a compensatory upregulation of c-abl with ensuing increase in matrix macropinocytosis in these cells. Although most of our studies were performed in the absence of TGF-␤1 stimulation, the signaling networks we studied are classically downstream from TGF-␤1 stimulation, and this growth factor did stimulate collagen internalization in our studies and in prior studies (18).…”
Section: C628mentioning
confidence: 49%
“…In the same study, Endo180 expression was observed in epithelial cells lining the ducts of glandular tissue affected by benign prostatic hyperplasia (BPH) or low-grade prostate cancer (5). Given that Endo180 expression and subcellular localization in constitutively recycling endosomes in mesenchymal-like tumor cells promote extracellular matrix (ECM) remodelling (6)(7)(8)(9)(10), disassembly of cell-cell and cell-matrix adhesions and cell motility (11,12), and enhanced tumor growth (7), we hypothesized that these pro-EMT properties are negatively regulated in normal prostate epithelial cells (PEC). In accordance, this study has identified a novel EMT-suppressor complex between the fourth of eight CTLDs, CTLD4, in Endo180 and the cell adhesion modulator CD147 that is indispensible for PEC stability.…”
Section: Introductionmentioning
confidence: 94%
“…Both pancreatic cancer cells and PSC are able to internalise collagen. Interestingly, the stimulation of epithelial-to-EMT TGF stimulates collagen endocytosis by cancer cells, via upregulation of Endo180 [44] (figure 3C).…”
Section: Ecm Internalisation and Cancermentioning
confidence: 99%